Reflections on the Scholarship of Teaching and Learning - Richard L. Miller (Park University, 2008)
At today's university the commitment to both scholarship and teaching seems incontrovertible. It is enshrined in mission statements, strategic plans, and promotion and tenure guidelines. This recognition of the University's dual purpose has led to an unfortunate division between teaching and research; a division recognized by the meta-analysis of 58 studies conducted by Hattie and Marsh (1996) that found no relationship between research productivity and teaching effectiveness. Their recommendation was that universities should aim to increase the circumstances where teaching and research meet.